2009
DOI: 10.1111/j.1365-2710.2008.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in combination with other antipsychotic drugs may worsen psychosis

Abstract: Aripiprazole is a new generation antipsychotic drug with a partial agonist effect on dopamine D2 and D3 receptors. We report the case of a schizophrenic patient whose symptoms worsened after adding aripiprazole to another antipsychotic drug (amisulpiride). The physiopathology of this process seems to be mediated through the dopaminergic effect of aripiprazole in hypodopaminergic environments, caused by the administration of antipsychotic drugs such as amisulpiride. Besides this, the chronic administration of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
1
21
1
Order By: Relevance
“…Concerns have been also voiced about increased risk of QT prolongation in concomitant use of ziprasidone with low-potency conventional antipsychotic medications (eg, thioridazine), 44 as well as worsening of psychosis due to displacement of antipsychotic medications from the D 2 receptor when aripiprazole is added as a concomitant treatment. 44,45 The evidence for combining antidepressants from different classes is somewhat stronger than other medica- 3,46,47 However, this option also should be considered only after optimal monotherapy and switching to an antidepressant from a different class have failed. 48 Furthermore, most available data on antidepressant combination therapy focus on patients with major depression.…”
Section: Commentmentioning
confidence: 99%
“…Concerns have been also voiced about increased risk of QT prolongation in concomitant use of ziprasidone with low-potency conventional antipsychotic medications (eg, thioridazine), 44 as well as worsening of psychosis due to displacement of antipsychotic medications from the D 2 receptor when aripiprazole is added as a concomitant treatment. 44,45 The evidence for combining antidepressants from different classes is somewhat stronger than other medica- 3,46,47 However, this option also should be considered only after optimal monotherapy and switching to an antidepressant from a different class have failed. 48 Furthermore, most available data on antidepressant combination therapy focus on patients with major depression.…”
Section: Commentmentioning
confidence: 99%
“…In addition, according to two Cochrane Databases of Systematic Reviews, while the use of depots continues to be based largely on clinical judgement, one long-term study showed that relapse was significantly reduced by fluphenazine decanoate [37,38]. Moreover, based on the existing results, in opposition to Adan-Manes et al [22], Takeuchi et al [23], and Letmaier et al [24], no worsening of psychosis was evident by combination of aripiprazole with flupenthixol in the present assessment. While undetected poor aripiprazole adherence could be one potential reason for final results that show enhancement with flupenthixol decanoate, it surely is not the only one.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of atypical antipsychotic drugs, too, are well tolerated and may be operative in the management of treatment-refractory schizophrenia and schizoaffective disorder [21]. Although some studies have found that in cases of treatment-refractory schizophrenia, where clozapine is supposed to be inappropriate, combination therapy with non-clozapine atypical antipsychotic drugs is an approach worthy of attention [22], primary case reports advise that aripiprazole combined with dopamine antagonists, with a high affinity for D2 and D3 receptors may worsen psychosis [22][23][24]. So it has been recommended by some researchers that, because of their lower D2 receptor affinity, clozapine and quetiapine might be a better choice for combined treatment with aripiprazole [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Such worsening has been noticed in adults who are on aripiprazole combination therapy (with other dopamine antagonists). [49] In situations where the patient was already taking dopamine antagonist and aripiprazole was added to it, a worsening of psychosis was observed. [49] The drug acts as a dopamine-receptor agonist in hypo-dopaminergic conditions and as an antagonist in hyper-dopaminergic state.…”
Section: Discussionmentioning
confidence: 99%
“…[49] In situations where the patient was already taking dopamine antagonist and aripiprazole was added to it, a worsening of psychosis was observed. [49] The drug acts as a dopamine-receptor agonist in hypo-dopaminergic conditions and as an antagonist in hyper-dopaminergic state. Hypersensitivity to dopaminergic agonist activity, especially with prior chronic administration of antipsychotic, has been proposed as an additional mechanism.…”
Section: Discussionmentioning
confidence: 99%